Analytical Approach For Enhanced Residue Modular Multiplier For Cryptography (International Journal of Engineering and Computer Science, 2015)
This paper presents an implementation of VLSI architecture for Dual Field Residue Arithmetic modular multiplier with less delay based on finite field arithmetic to support all public key cryptographic applications. A new method for incorporating Residue Number System (RNS) and Polynomial Residue Number system (PRNS) in modular multiplication is derived and then implemented VLSI Architecture for dual field residue arithmetic modular multiplier with less delay. This architecture supports the conversions, modular multiplication for polynomials and integers and modular exponentiation in same hardware. This architecture has a carry save adders (CSAs) and parallel prefix adders in MAC units to speed up the large integer arithmetic operations over GF (P) and GF (2n), hence this reduces the delay up to 10 percent.